Jacks of All Trades and Masters of None: Audiences' Reactions to Spanning Genres in Feature Film Production - Hsu, Greta (Administrative Science Quarterly, 2006)
Through analyses of audience reception of U.S.-produced feature film projects from the period 2000–2003, I develop insight into the trade-off assumed in organizational ecology theory between an organization's niche width and its fitness. This assumption, termed the principle of allocation, holds that the greater the diversity in regions of resource space targeted by an organization, the lower the organization's capacity to perform well within them. Using data at both the professional critic and consumer levels, I demonstrate the empirical validity of this principle: films targeting more genres attract larger audiences but are less appealing to those audience members. Moreover, I find that audiences' perceptions of a film's fit with targeted genres drive this trade-off, as multi-genre films are difficult for audiences to make sense of, leading to poor fit with tastes and lowered appeal. These findings highlight the key role audiences' perceptions play in the trade-offs associated with different niche strategies.